Strengthening Internal Factors for Campuspedia Start-Up Growth - Rayis, Hasan; Gamaputra, Gading; Yudheyaningrum R, Ester (KnE Social Sciences, 2022)
Campuspedia is well-known in the millennial generation as an educational start-up platform that provides information about lectures, scholarships, and the State Higher Education exams. Campuspedia has made significant progress in developing its system to make it more user-friendly for high school students, college students, and recent graduates. Its relatively good start-up growth was influenced by internal factors that cannot be ruled out from the company’s perspective. The four major components of these internal factors were marketing, human resources, finance, and operational/technical. The purpose of this research was to look at the internal factors that influenced the growth of the Campuspedia start-up company using descriptive methods and a qualitative approach. Internal factors were important components that had to be managed properly from the company’s perspective to accelerate the growth of the start-up. Internal factors led to better growth due to the advancement of a website system that facilitated the experience for consumers and followers, social media that contained useful content, reasonably good financial management, and good employee management. According to the research, businesses should implement a control system in all aspects of their operations, as well as good communication between the core team and new hires and interns. Keywords: start-up, internal factors, growth